INTERPRETING THE ABSURD THEATRE THROUGH EXISTENTIALISM APPROACH - Sutjiati, Rita; Ningsih, Tri Wahyu Retno; Budiwaty, Suci (Prosiding PESAT, 2015)
Absurdity which is a form of human existence is the dominant theme to express human viewof life. Albert Camus, a French writer, was well known for his philosophycalled absurdism which has some similarities with existentialism. Introducing the concept of absurd theater in a foreign language to a group of literature students is not an easy task. Therefore, it is necessary to find an ideal approach to enhance students in this theater course and facilitate them for literature understanding through several literature theories. This study proposed sociological literature approach with two elements involved, the sociology of the author and the sociology of literature, in order to help students understand the absurdity of literary works. Existentialism approach was also used to solve the complexity of concepts in each drama scripts. Through the two elements of the sociology of literature, we acquired that the essence of existentialism is the term „exist‟, as Camus‟s work on rebellion theme, „I rebel; therefore I exist‟. The root of absurdity is absurdity itself. Therefore, talking about the absurdity of literary works is talking about the notion of absurdity itself and the notion of its feeling, and then about attitudes determine our actions. Absurdity also need to be explored through emotions and intertextuality.